Women without a past? : German autobiographical writings and fascism - Sayner, Joanne (Genus--gender in modern culture, 2007)
Who remembers, and how? Debates about the role of memory as history - and of literature as memory - have increasingly come to fascinate those interested in how we look at our pasts as a means for understanding the present. Women without a Past? brings together for the first time autobiographies written by seven women who experienced Nazism from different perspectives: Elfriede Brüning, Hilde Huppert, Greta Kuckhoff, Elisabeth Langgässer, Melita Maschmann, Inge Scholl, and Grete Weil. Their autobiographies provoke diverse and challenging answers to questions about who remembers what, when, whe.